Description of The Attitude and Behavior of The Patient with Diabetes Mellitus Type II in Management of Hypoglycemia at Puskesmas III Denpasar Utara - I Ketut Alit Wira Permana; I Kadek Artawan (Babali Emergency and Disaster Research, 2023)
Introduction : Diabetes Mellitus is a worldwide health problem, threatening and growing rapidly, resulting in morbidity and premature mortality. Diabetes Mellitus is included in the four dangerous non-communicable diseases which cause 50 million deaths each year. Diabetes Mellitus is a major health problem that causes disability and death. One of the causes of increased mortality in diabetes mellitus is the patient experiencing hypoglycemia. Hypoglycemia is a health disorder that occurs when blood sugar levels are below normal levels. Hypoglycemia is the most common complication in individuals with diabetes. Method: This scientific writing uses a descriptive method with a quantitative approach using a measuring instrument questionnaire and the sampling technique used is total sampling with a total sample of 85 respondents. The method of collecting data is by distributing questionnaires. Data were analyzed by univariate analysis Results: The results of this study found that the majority of respondents had a positive attitude as many as 78 people (91.8%), a negative attitude as many as 7 people (8.2%) and had a positive attitude as many as 78 people (91.8%), negative behavior as many as 7 people (8.2%) .